Case Report: An Unusual Case of Pheochromocytoma - Liao, Ying; Shi, Shanshan; Liao, Lihua; Zhao, Yukun; Lin, Rongwen; Chen, Kaihong (Frontiers in Cardiovascular Medicine, 2022)
Pheochromocytoma is a benign catecholamine secreting tumor which is rare and originating from the adrenal gland. It has been known for a wide range of clinical manifestations and can mimic other difficult to diagnose diseases. Here, we report a female patient with acquired long QT syndrome, a rare complication of pheochromocytoma. Although relatively rare, the presence of pheochromocytoma should be considered in the case of malignant arrhythmias and electrocardiographic changes in patients.